Relationship Between Parental Communication Patterns and Language Delay in Preschool Children (4–6 Years) - Andi Akifa Sudirman; Dewi Modjo; Sitti Mutmainah Gobel (Pusat Penelitian dan Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2026)
Background: The family is the primary environment that supports children's language development, especially during the preschool years (4–6 years). However, many parents assume that language development occurs naturally without adequate verbal interaction. This study aimed to examine the relationship between parental communication patterns and the risk of language developmental delay among preschool children. Methods: A quantitative correlational study with a cross-sectional design was conducted at TK Handayani Telaga Biru. A total of 45 mother-child pairs were selected from 70 preschool children using purposive sampling. Parental communication patterns were assessed using a modified 25-item questionnaire covering five interpersonal communication dimensions (Cronbach’s alpha = 0.854). The risk of language developmental delay was evaluated using the language sector of the Denver Developmental Screening Test II (Denver II). Data were analyzed using the Continuity Correction Chi-Square test. Results: Most mothers demonstrated ineffective communication patterns (57.8%, n = 26), while more than half of the children were categorized as having suspected language developmental delay (53.3%, n = 24). Statistical analysis showed a significant relationship between parental communication patterns and the risk of language developmental delay among preschool children (p = 0.005). Conclusion: Ineffective parental communication patterns are significantly associated with a higher risk of language developmental delay in preschool children. Parents should be encouraged to use open, responsive, and supportive communication to promote optimal language development during early childhood